2012
DOI: 10.1016/j.hrthm.2012.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac J-point elevation before the onset of polymorphic ventricular tachycardia and ventricular fibrillation in patients with an implantable cardioverter-defibrillator

Abstract: Background The clinical importance of the J-point elevation on ECG is controversial. Objective Study intracardiac J-point amplitude before ventricular arrhythmia. Methods Baseline 12-lead ECGs and far-field (FF) right ventricular (RV) intracardiac ICD electrograms (EGMs) were recorded at rest in 494 patients [mean age 60.4±13.1; 360 (72.9%) men] with structural heart disease [278 (56.3%) ischemic cardiomyopathy] who received primary [463 (93.9%) patients] or secondary prevention ICD. Ten-second intracardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recent clinical studies investigating the predictive role of intracardiac electrograms to detect life‐threatening ventricular arrhythmias or flow‐limiting coronary obstruction have successfully demonstrated that intracardiac ST‐segment monitoring can predict arrhythmic events. Specifically, Fischell et al reported early detection of the presence of acute MI in patients at high risk for acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent clinical studies investigating the predictive role of intracardiac electrograms to detect life‐threatening ventricular arrhythmias or flow‐limiting coronary obstruction have successfully demonstrated that intracardiac ST‐segment monitoring can predict arrhythmic events. Specifically, Fischell et al reported early detection of the presence of acute MI in patients at high risk for acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…ST‐segment changes have been well established as strong predictors of acute MI and VTEs . Also, several studies have reported changes in the depolarization phase following acute MI, in both animals and humans …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both J-waves and J-point elevation (JPE) with a notch or slur have been associated with an increased risk of ventricular fibrillation and polymorphic ventricular tachycardia in several studies (23-25). At the same time, J-point elevation known as benign early repolarization, is a common finding in healthy young people and is particularly prevalent in patients of African descent.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Analysis of intracardiac electrograms (EGMs) is a vital part of ICD function [1-4]. Vectorcardiogram (VCG) characterizes movement of the heart vector over the cardiac cycle and was proven to be more informative than projection of the heart vector on a limited number of leads axes.…”
mentioning
confidence: 99%